Elections in Africa and China’s Position: African Opinion - Deych, Tatiana (Africana Studia, 2020)
Almost half of African conflicts are “post-electoral”, aroused by disputed claims over legitimacy of the elections, including leaders staying in power past a designated two-term limit. Substantial proportions of the population in Africa are skeptical about the quality of their elections. They talk about vote manipulation, lack of transparency of election monitoring bodies and corruption. Poor electoral process produces public mistrust, protest, and violence. The most serious problem is interference of external forces into election process. The US brings which is essential to growth and stability, while the West model places a premium on human rights and democracy. Most Africans believe that food, shelter and health are more important than the right to vote. So they make a choice for the Beijing Model instead of the Washington Consensus. But Zambia has become one of the first African countries where China’s role turned into potent political issue. Michael Sata anti-Chinese sentiment helped him to defeat President Rupiah Banda on the elections of 2011. Оn the eve of Zambia’s presidential elections one of the most common tropes about the vote was to describe it as a referendum on China.